Mobile balanced and healthy diet on android system / Mohamad Khairul Amir Zaidan - Zaidan, Mohamad Khairul Amir (2015)
Healthy Diet is all about taking nutrition food to stay healthy, by providing information about calorie intake per day and assist the user to maintain diet lifestyle.Nowadays, many people have low concern on diet lifestyle. With this application it will process all the data insert by the user such as height, weight, age, gender to calculate user Basal Metabolic Rate (BMR), this calculation is the rate that maintaining body weight and how much it burns per day. Then when BMR is calculated, Daily Calorie Required (DCR) calculation is taken to know the intake calorie per day of that particular person. By identifying user Level of Activity (LOA), DCR can be calculated by multiplying BMR with LOA, then get the result of DCR. By using rule based method to analyze all data input by user so that the rule will selected on what group of BMI of the user. In addition, Rapid Application Development method is applied in this development since it is fast and can overlap from interface and development and testing. By the month passing, user can loss about 1 to 2 kilogram based on what eating dietary been suggested. This system gives result of 65 percent who used the application gain more knowledge on diet lifestyle and reduce their weight.